Hi All,
I am stuck up at the following step. It will be great if someone can help me out:
2 = λfx.f(f x)
3 = λfx.f(f(f x))
ADD = λm n f x. m f (n f x)
My steps are:
(λm n f x. m f (n f x)) (λf x.f(f(f x))) (λf x.f(f x))
-> ((λn f x. (λf x.f(f(f x))) f (n f x))) (λf x.f(f x))
-> ((λf x. (λf' x'.f'(f'(f' x'))) f ((λf" x".f"(f" x")) f x)
Is the parenthesis fine? I really confuse myself on the substitutions and parenthesis. Is there a formal, easier technique to address such problems?
regards, darkie